Dampak Implementasi Sales Promotion Dalam Meningkatkan Repurchase Intention Pada Belikopi Kota Semarang - Agustinus, Deo Viandra; Putra, Febrianur Ibnu Fitroh Sukono; Hariyadi, Guruh Taufan; Kusuma, Pradana Jati (Politeknik Negeri Ambon, 2024)
The food and beverage industry that is growing very rapidly is the coffee shop. This business competition is very tight so companies need to create products that suit consumer tastes. The coffee shop in question is BeliKopi. This research aims to examine the influence of customer experience, brand trust on repurchase intentions with sales promotions as moderating variables at Belikopi in Semarang City (Central Semarang). The method used in this research is sampling purposes using 103 respondents using questionnaires distributed via Google from. In the data analysis process using SmartPLS version 4. The research results show that customer experience and brand trust have a significant positive effect on repurchase intention, while customer experience and brand trust do not have a significant positive effect on repurchase intention which is moderated by sales promotions at Belikopi in Semarang City (Central Semarang).